PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA INDEKS LQ 45 DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Ni Kadek Alit Budiartini; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The company value is used as an assessment by investors regarding the success of a company which is often related to the stock price. The high share price also makes the company value high. A high company value will make the market believe not only in the company's current performance but also in the company's future prospects. This study aims to test and obtain empirical evidence of the effect of leverage, company size and managerial ownership on firm value at LQ 45 companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The research population is LQ 45 companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The sample in this study were 135 LQ 45 companies which were determined based on the purposive sampling method. The analytical tool used to test the hypothesis is linear regression analysis. The results showed that leverage, managerial ownership had no effect on firm value. Meanwhile, company size has a negative and significant effect on firm value. Further research can develop this research by using other variables which theoretically have an influence on firm value such as Profitability, Liquidity, Dividend Policy, Capital Structure, and others